Comparative analysis of Mobile Crowdsensing and Ecological Momentary Assessment systems - Michael Stach; Adnan Ramović; Manfred Reichert; Rüdiger Pryss (Ecological Informatics)
The increasing ubiquity of smartphones and the growing focus on health and wellness have significantly boosted the popularity of mobile health (mHealth) apps. With over 500 million users worldwide incorporating these apps into their health management practices, the innovative utilization of built-in smartphone sensors like cameras and microphones stands out. This approach not only monitors health conditions but also promises to broaden the accessibility and enhance the quality of healthcare for a diverse patient population. In the realm of mobile sensing, various applications exhibit either similar system architectures or distinct, innovative solutions. However, a comprehensive understanding of these technologies remains limited due to the scarcity of scientific literature that thoroughly analyzes and describes these systems and their applications. This paper aims to bridge this gap by providing a critical examination of the existing technology based on systematic analyzes of mHealth systems, specifically focusing on Mobile Crowdsensing (MCS) systems and Ecological Momentary Assessment (EMA) apps. This endeavor seeks to critically and profoundly map out the current state of mHealth architectures and applications. In accordance with the PRISMA guidelines, a comprehensive examination of 158 MCS systems and 292 EMA applications in the Google Scholar, PubMed, PsycINFO, and Web of Science databases was conducted through two distinct analyses. The reviews identified a growing trend in MCS and EMA research, exploring aspects such as participatory versus opportunistic sensing, availability on app stores, operating systems, sensor implementation, assessment types, notification methods, and reminder mechanisms, alongside a broad categorization of use cases. This comprehensive overview and the in-depth analysis of selected systems are intended to serve as a valuable resource for both researchers and practitioners. By critically highlighting the evolving landscape of MCS and EMA applications, this paper underscores the potential of mHealth to transform healthcare accessibility and efficacy.